KAJIAN PERENCANAAN DAN PENGANGGARAN KESEHATAN DI DINAS KESEHATAN KOTA PADANG TAHUN 2006 - Denas Symond (Faculty of Public Health, Andalas University, 2007)
Padang Panjang. Data were collected through questioners and assessment of body mass index. This study revealed that social economic, genetic and carbohydrate consumption contribute to the development of overweight among those subyects and suggest among others to those who are incharge in public health nutrition should give detail information on the risk, causes and prevention of overweight. Health development is one of the supporting National Development that requires availability in quantity and quality of human resources adequately especially at District level. In health planning needed the person who know to determine their own priority on local health development based on local ability, condition and hence it is expected health planned made could solve health problems in their area. The study was meant to know annual health planning processes and problems concerning the implementation in District Health Officee Padang City municipality. This was an qualitative study who interviewed 26 informans consist of: Head of District Health Office, Head of Administrative Officee, Sub-Division Head of Planning and Budgetting and representative of 8 Health Centree Officee Head and 8 Health Centree Officee Admin Head at Padang city municipality.Data were collected by six interviewer who already trained and qualitively analyzed by researcher. The result of study showed that health planning process done by bottom-up planning. Most of members who involved in health planning did not have good understanding on planning methods and the execution of planning steps. Some constrains that found were unavailability and unaccuracy data for making health planning. Health planning documents made namely Budgetting Plan of Working Unit (Rencana Anggaran Satuan Kerja). Annual budget in the year 2006 increased 3.8% than the year before. It was concluded that annual health planning done by buttop-up planning and unproperly health planning caused by some members who involved in health planning did not have good understanding on planning methods and the execution of planning steps.It was recommended to District Health Officee to gain his staff in health planning by training in the scope of health planning steps.